A rare mechanism of delayed splenic rupture following the nonoperative management of blunt splenic injury in a child - Toko Shinkai; Kentaro Ono; Kouji Masumoto; Yasuhisa Urita; Chikashi Gotoh (Surgical Case Reports)
Abstract Background Nonoperative management (NOM) has been established as the standard treatment for isolated blunt organ injury in hemodynamically stable pediatric patients. Although delayed splenic rupture or bleeding is a rare complication in NOM, it is an issue that many pediatric surgeons are greatly concerned about. We herein report a rare pediatric case concerning the mechanisms involved in delayed splenic rupture after NOM. Case presentation A 9-year-old boy with severe abdominal pain was transferred to our hospital. Twenty-one hours before the admission, he had been kicked in the region of his left lateral abdomen. Contrast-enhanced abdominal computed tomography revealed a severe intra-parenchymal hematoma and multiple lacerations of the spleen with a large amount of hemoperitoneum without active bleeding. His condition was diagnosed as a grade III injury on the AAST splenic injury scale. After fluid resuscitation, his vital signs became stable. The patient was treated with NOM in our intensive care unit. However, suddenly after defecation (72 h after the injury), he started complaining of severe abdominal pain and left shoulder pain. His blood pressure dropped to 70/35 mmHg, and he started to lose consciousness. Abdominal ultrasonography (US) revealed increased ascites. Fluid resuscitation and blood transfusion were performed. His symptoms and abdominal US findings suggested that splenic re-bleeding had caused delayed splenic rupture to occur. Emergency splenectomy was performed. The resected spleen was enlarged with a large parenchymal hematoma. The posterior-lateral side of the splenic capsule was ruptured. Conclusions The mechanism of delayed splenic rupture in our case was considered to be the result of a tear in the subcapsular hematoma caused by stretching the splenocolic ligament related to a bowel movement during defecation. Although delayed splenic rupture or bleeding is unpredictable, it is very important to understand the mechanisms and to educate the family of the children with splenic injuries of the warning signs of delayed rupture or bleeding.